2005
DOI: 10.1021/jo050117b
|View full text |Cite
|
Sign up to set email alerts
|

Organohypervalent Iodine:  Development, Applications, and Future Directions

Abstract: The synthetic utility of organohypervalent iodine reagents will be illustrated by their use in the alpha-hydroxydimethylacetal formation reaction from enolizable ketones, alpha-hydroxylation, alpha-tosyloxylation, alpha-alkoxylation and arylation of ketones, carbon-carbon bond formation, and intramolecular cyclopropanation using iodonium ylides. The uses of these reagents in the Hunsdiecker reaction of carboxylic acids and Hofmann rearrangement of carboxamides is presented. Specific transformation in the cuban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(108 citation statements)
references
References 118 publications
1
105
0
2
Order By: Relevance
“…Slower reaction was observed using 0.1 eq of 4-iodoanisole (entry 13). However, larger amounts (0.5-1 eq) led to decreased reaction times with similar yields of 3a (entries 14,15).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Slower reaction was observed using 0.1 eq of 4-iodoanisole (entry 13). However, larger amounts (0.5-1 eq) led to decreased reaction times with similar yields of 3a (entries 14,15).…”
Section: Resultsmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, these reagents are highly expensive. And stoichiometric amounts of iodine reagents are required to produce equimolar amounts of organic iodine waste.…”
mentioning
confidence: 99%
“…For a more comprehensive discussion of the numerous significant contributions made to this field by Moriarty's group, including α-hydroxylation of acetals, which falls outside the scope of this article, the 2005 review article is referred to. [56] Polymer-supported hypervalent iodine reagents have also found application in the α-hydroxylation of ketones. Togo et al reported a method similar to Moriarty's PIDA-mediated hydroxylation reaction using poly[4-(diacetoxyiodo)styrene] under basic conditions.…”
Section: Hydroxylationmentioning
confidence: 99%
“…The butane-1,4-dione products were formed in moderate yields. [56,136] The groups of Caple and Zefirov later developed iodosobenzene tetrafluoroborate and iodosobenzene hexafluorophosphate as stable and superior reagents for the homocoupling of TMS enol ethers (Scheme 70). [137] These reagents were also efficient in the coupling of aliphatic substrates.…”
Section: Homocouplingmentioning
confidence: 99%
“…Thus, alternative methods for this transformation are desirable. Organohypervalent iodine reagents [10][11][12][13][14][15][16][17][18][19] have been increasingly used in contemporary organic synthesis. In particular, organoiodine(III) reagents, namely (diacetoxyiodo)benzene, 20 bis(trifluoroacetoxy)iodobenzene, 21 [hydroxy(tosyloxy)iodobenzene] 22 and iodosobenzene (IOB) 23 have emerged as versatile oxidizing agents.…”
Section: Introductionmentioning
confidence: 99%